2007
DOI: 10.1016/j.bbamcr.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Raf kinases: Function, regulation and role in human cancer

Abstract: The Ras-Raf-MAPK pathway regulates diverse physiological processes by transmitting signals from membrane based receptors to various nuclear, cytoplasmic and membrane-bound targets, coordinating a large variety of cellular responses. Function of Raf family kinases has been shown to play a role during organism development, cell cycle regulation, cell proliferation and differentiation, cell survival and apoptosis and many other cellular and physiological processes. Aberrations along the Ras-Raf-MAPK pathway play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
215
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(222 citation statements)
references
References 188 publications
(313 reference statements)
3
215
0
4
Order By: Relevance
“…Knockout of C-Raf in mice or in C-Raf-deficient cells can cause Fas-induced apoptosis (43,60). We observed that transfection of ODN-Raf led to a significant detachment of transfected cells and loss of viability as determined by an MTS assay.…”
Section: Discussionmentioning
confidence: 77%
“…Knockout of C-Raf in mice or in C-Raf-deficient cells can cause Fas-induced apoptosis (43,60). We observed that transfection of ODN-Raf led to a significant detachment of transfected cells and loss of viability as determined by an MTS assay.…”
Section: Discussionmentioning
confidence: 77%
“…The major BRAF functions are believed to be mediated by phosphorylation and thus activate the MAPK1, MAP2K1, and MAP2K2 pathways. 118,214 Mutations in BRAF have been shown to impair responsiveness to Figure 8 Alternative algorithm for molecular testing for patients with lung adenocarcinomas. Approximately 25% of lung adenocarcinomas harbor KRAS mutations, which predict non-response to EGFR TKI therapy.…”
Section: Braf Mutationmentioning
confidence: 99%
“…S4). Ras propagates incoming messages from membrane growth factor receptors (e.g., EGFR) to downstream proteins such as Raf at defined l d lipid microdomains in the plasma membrane (15,16). As such, its translocation to the cytoplasm greatly affected the proliferative Ras/MAPK signaling, which is frequently overactive in cancer cells and responsible for their loss of differentiation (17,18).…”
Section: Ohoa Inhibits the Egfr/ras/map Kinase And Pi3k/akt Pathways Inmentioning
confidence: 99%